ANALISIS MANAJEMEN ASET TETAP PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN TANA TORAJA - Jannah, Fachriyahthul; Muamilah, Husnul; Yulianadewi, Ina (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
This research aims to find out how fixed asset management is managed in Tana Toraja Regency. This research uses a descriptive qualitative approach. The location for this research was carried out at the Tana Toraja Regency Regional Financial and Asset Management Service office. Data collection was carried out by means of interviews, observation and documentation. The research data collection procedure uses two types of data, namely primary data and secondary data. It can be concluded that asset management in Tana Toraja Regency has largely been running in accordance with the applicable statutory regulations as regulated by Tana Toraja Regency Regional Regulation No. 4 of 2015 concerning Management of Regional Property, but it has not been fully maximized and there are still many deficiencies. There are several assets that receive less attention, thus affecting the LKPD (Regional Government Financial Report) to BPK (Financial Audit Agency) reporting process related to regional asset management. Asset management has been running in accordance with the regional asset management cycle in general, although it has not been running optimally.